In vitro activity of BaH1, the main hemorrhagic toxin of Bothrops asper snake venom on bovine endothelial cells - Borkow, Gadi (1995)
Incubation of BaH1, the main hemorrhagic toxin purified from the venom of Bothrops asper, with endothelial cells caused the appearance of spaces among the cells. This effect became more noticeable with increasing hemorrhagin concentration and longer incubation time. Later, the cells became rounded and detached from the substrate into the medium. Augmentation of Trypan blue did not stain the detached cells, indicating their viability. Moreover, after washing the floating cells from the toxin they could be recultivated: they again spread on the substrate and proliferated, demonstrating that BaHl is not directly cytotoxic to the endothelial cells